Design and Prototyping of Remote Current, and Temperature Monitoring System for Distribution Transformers. - Bwengye, Duncan (Kabale University, 2023)
The distribution network in a power system has the highest commercial risk and therefore needs adequate and regular monitoring of critical equipment, distribution transformers being top priority since they are the backbone of the distribution network. The work in this report emphasizes the need for remote monitoring and the design of remote monitoring system for this critical equipment. Chapter One discusses the background of the problem, problem statement, objectives of the research, and its significance. Chapter two discusses the literature review, related research, tools and materials used to carry out the research and building the prototype for proof of concept. Chapter three describes the methods used to achieve the main objective and specific objectives of the research. Chapter four discusses in detail the simulations, experiments, procedure and precautions taken while carrying out the experiments and building the prototype. The results of the experiments, milestones achieved are also discussed in this chapter. The conclusions from this research and recommendations for future improvements are discussed in chapter five.